IMPROVING OCCUPATIONAL HEALTH AND SAFETY KNOWLEDGE THROUGH COUNSELING FOR CONSTRUCTION WORKERS AT THE MITRA KELUARGA BSD HOSPITAL PROJECT - Lailatul Qomariyah; Muhammad Zulfikar Adha; Syaiful Bahri; Lela Kania Rahsa Puji; Frida Kasumawati; Novita Faulian Syahrani; Ayu Syafitri; Meilina Ardela (Gapura (Garba Pembangunan Masyarakat), 2026)
This community service activity aims to improve the knowledge and compliance of construction workers with occupational safety and health (K3) through counseling at the Mitra Keluarga BSD Hospital Project of PT. Tatamulia Nusantara Indah. The activity methods include K3 counseling, training on the use of PPE, and evaluation through pre-tests and post-tests. A total of 24 workers participated in this activity. The results showed an increase in knowledge scores from an average pre-test score of 94.1 to 91.25 in the post-test, and 79% of workers experienced an increase in scores after the training. The training also increased understanding of work hazards, safety procedures, and the use of PPE. Thus, the K3 counseling and training program has proven effective in increasing workers' awareness and ability to implement occupational safety. This activity is recommended to be carried out periodically to strengthen the K3 culture in construction projects.